Integrasi Gaya Belajar dan Nilai-Nilai Pendidikan Islam dalam Meningkatkan Kemandirian Belajar Siswa Madrasah - Syahrisshobirin Syahrisshobirin; Ali Umar; Ridho Baihaqi; Siti Khodijah; Masyitah Masyitah (Tarbiyatuna Kajian Pendidikan Islam, 2025)
This study aims to examine the integration of learning styles and Islamic educational values in fostering students' learning autonomy in madrasahs. In the context of Islamic education, the development of learning independence is not solely based on students’ learning style preferences but must also be grounded in core Islamic values such as responsibility, discipline, and sincerity in seeking knowledge. This research employs a qualitative approach using a case study method at a Madrasah Tsanawiyah in North Sumatra. Data were collected through participatory observation, in-depth interviews with teachers and students, and analysis of instructional documents. The findings indicate that teachers’ understanding of diverse learning styles—visual, auditory, and kinesthetic—enables them to design more responsive and meaningful learning experiences. The integration of Islamic educational values is implemented through the habituation of positive behavior, the cultivation of intrinsic motivation based on spirituality, and character reinforcement throughout the learning process. The synergy between pedagogical strategies based on learning styles and Islamic values has proven effective in enhancing students’ learning autonomy, particularly in aspects such as learning planning, time management, and decision-making in the learning process. These findings affirm the importance of combining modern pedagogical approaches with Islamic values to develop students who are independent both academically and spiritually.